2019
DOI: 10.1029/2019gl085014
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Nongyrotropic Electron Distribution Across the Electron Diffusion Region in the Magnetotail Reconnection

Abstract: Using measurements by the Magnetospheric Multiscale spacecraft in the magnetotail, we studied electron distribution functions across an electron diffusion region. The dependence of the nongyrotropic distribution on the energy and vertical distance from the electron diffusion region midplane was revealed for the first time. The nongyrotropic distribution was observed everywhere except for an extremely narrow layer right at the electron diffusion region midplane. The energy of the nongyrotropic distribution incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 41 publications
(60 reference statements)
8
26
0
Order By: Relevance
“…These strong currents were verified to be carried by the electrons (Li et al, 2019;Huang et al, 2018;Wang et al, 2018;Zhou et al, 2019) and will be analyzed later in their individual local current coordinates. The local current system in Event I was derived from minimum variance analysis (Paschmann & Schwartz, 2000) The details on the choice of the local current system can be found in Li et al (2019). Because the four MMS satellites passed through the electron current layers one after another, the Timing method (Schwartz, 1998) was used to estimate the current layer velocity and the thickness.…”
Section: Observation and Analysismentioning
confidence: 85%
See 3 more Smart Citations
“…These strong currents were verified to be carried by the electrons (Li et al, 2019;Huang et al, 2018;Wang et al, 2018;Zhou et al, 2019) and will be analyzed later in their individual local current coordinates. The local current system in Event I was derived from minimum variance analysis (Paschmann & Schwartz, 2000) The details on the choice of the local current system can be found in Li et al (2019). Because the four MMS satellites passed through the electron current layers one after another, the Timing method (Schwartz, 1998) was used to estimate the current layer velocity and the thickness.…”
Section: Observation and Analysismentioning
confidence: 85%
“…, as an indication of in the EDR proximity (Burch et al, 2016;Egedal et al, 2016;Hesse et al, 2014;Li et al, 2019;Torbert et al, 2018), was observed. Thus, we conclude that the current layer in Event I was an EDR.…”
Section: Observation and Analysismentioning
confidence: 85%
See 2 more Smart Citations
“…Earlier studies of this current sheet 8,11 reported established signatures of EDRs 4,9 , including oppositely-directed electron jets with a speed exceeding -1 ( Fig. 2c), crescent-shaped electron velocity distributions and magnetic-to-particle energy conversion.…”
mentioning
confidence: 67%